2018
DOI: 10.3390/ijerph15040785
|View full text |Cite
|
Sign up to set email alerts
|

Stress and Alterations in the Pain Matrix: A Biopsychosocial Perspective on Back Pain and Its Prevention and Treatment

Abstract: The genesis of chronic pain is explained by a biopsychosocial model. It hypothesizes an interdependency between environmental and genetic factors provoking aberrant long-term changes in biological and psychological regulatory systems. Physiological effects of psychological and physical stressors may play a crucial role in these maladaptive processes. Specifically, long-term demands on the stress response system may moderate central pain processing and influence descending serotonergic and noradrenergic signals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 68 publications
1
34
0
1
Order By: Relevance
“…Psychosocial stress has a direct impact on both people´s health and pain processing. 3,7,8 Stress is an individual´s reaction to external or internal stressors activating psychological and physiological mechanisms, which prepare the individual to deal with an upcoming challenging situation. [9][10][11] Stressors that combine social evaluative threat and uncontrollability are powerful in activating stress reactivity systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Psychosocial stress has a direct impact on both people´s health and pain processing. 3,7,8 Stress is an individual´s reaction to external or internal stressors activating psychological and physiological mechanisms, which prepare the individual to deal with an upcoming challenging situation. [9][10][11] Stressors that combine social evaluative threat and uncontrollability are powerful in activating stress reactivity systems.…”
Section: Introductionmentioning
confidence: 99%
“…7,13 These mechanisms are highly interrelated to pain processing. 7,8,11 For example, the occurrence of critical life events may elicit central changes in the limbic system and related neurotransmitters, which then alter descending signaling pathways and change pain inhibitory mechanisms. Chronic stress, on the other hand, and the resulting change of the body´s ability to maintain homeostasis may alter ascending signaling mechanisms and lead to decreased pain thresholds.…”
Section: Introductionmentioning
confidence: 99%
“…After all, such effects can depend on the individual risk profile of a person on the one hand and on the reinforcing mechanisms of action of different therapy modules on the other. Regarding exercise therapy, there are indications that psychosocial factors may influence physiological exercise adaptation outcomes [12][13][14][15]. For example, it has been shown that the individual distress level influences the exercise dose-response effect on pain and depression outcomes, whereby a high exercise dose leads to worse outcomes because of additional high stress levels [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…As it was shown that MBSR is powerful in increasing stress resilience [48], this association may additionally reinforce the intended pathways through the combination of exercise and distraction [49]. Because stress and pain stimuli are processed in the same brain areas, additional effects on central and peripheral sensitization may therefore be expected [14]. One component of the MBSR-the body scan-is a training unit in which participants focus on different parts of bodily awareness which was shortened to 10 minutes [50] and offered directly after the sensorimotor training.…”
Section: Rationale Of Selectionmentioning
confidence: 96%
“…Although addressing all the underlying components of LBP earlier in the chronification process may yield broader benefits for both patient and the health care systems, interdisciplinary therapies tend to only be available for patients in the advanced stages of LBP. Secondly, the widely accepted biopsychosocial model of chronic pain [13] not only suggests that biological, social, and psychological factors contribute to the development of chronic pain, but also that there are interactions between these dimensions [14]. Therefore, an interdisciplinary intervention that takes into account these interactions is likely to be more effective.…”
Section: Introductionmentioning
confidence: 99%